Early Radiographic Outcomes of Minimally Invasive Chevron Bunionectomy Compared to the Modified Lapidus Procedure. Issue 3 (July 2022) - Cody, Elizabeth A.; Caolo, Kristin; Ellis, Scott J.; Johnson, A. Holly
Background: Minimally invasive (MIS) bunion surgery has become increasingly popular. Although early reports on outcomes have been encouraging, no study to date has compared outcomes from the MIS chevron and Akin procedures to the modified Lapidus procedure. Our primary aim was to compare early radiographic outcomes of the MIS chevron and Akin osteotomies to those of the modified Lapidus procedure in patients with comparable deformities, and secondarily to compare clinical outcomes. Methods: Patients were retrospectively reviewed for inclusion from a prospectively collected foot and ankle registry. Patients were eligible if they underwent either the MIS bunionectomy or modified Lapidus procedure and had preoperative and minimum 5-month postoperative weightbearing radiographs. Forty-one patients who underwent MIS bunionectomy were matched to 41 patients who underwent Lapidus bunionectomy based on radiographic parameters. Demographics, radiographic parameters, complications, reoperations, and PROMIS scores were compared between groups. Results: Both groups achieved similar radiographic correction. There was no significant difference in pre- or postoperative PROMIS scores between groups. Procedure duration was significantly faster in the MIS group ( P < .001). Bunion recurrence (hallux valgus angle ≥20 degrees) occurred in 1 MIS patient and 2 Lapidus patients, with all patients asymptomatic. The most common reason for reoperation was removal of hardware (4 patients in the MIS group, 2 patients in the Lapidus group). Conclusion: This is the first study to our knowledge to compare early radiographic outcomes between MIS bunionectomy and the modified Lapidus procedure in patients matched for bunion severity. We found that patients with similar preoperative deformities experience similar radiographic correction following MIS chevron and Akin osteotomies vs modified Lapidus bunionectomy. Further research is needed to investigate satisfaction differences between the procedures, longer-term outcomes, and which deformities are best suited to each procedure. Level of Evidence: Level III, Retrospective case control study.